PENGARUH KOMBINASI KONSENTRASI RAGI DAN LAMA FERMENTASI TERHADAP KADAR BIOETANOL DARI FERMENTASI LIMBAH KULIT PISANG BARANGAN (Musa acuminate colla) SEBAGAI RANCANGAN MODUL PEMBEAJARAN MATERI BIOTEKNOLOGI KONVENSIONAL SMA - Monalysa Monalysa; Imam Mahadi; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The research to determines yeast concentration effect and fermentation time of barangan skin waste (Musa acuminata colla) against bioethanol level and produce a learning module design of senior high school in conventional biotechnology material. The experimental research by conducting combination experiments of yeast concentration are 6 grams, 8 grams, 10 grams, and 12 grams which are combine with 72 hours, 120 hours, 128 hours, and 216 hours. The experiment was carried out with 4 treatments and 3 replications where the substrate was hidrolized by sulfuric acid (H2SO4) 0,5 M and continued with the development of learning module from experimental research data (only at the analysis and design stages). The research data were analyzed by analysis of varians (ANAVA) and continued by the Tukey test on 5% level. The results showed that yeast concentration and fermentation time had a significant effect on bioethanol levels but had no effect on the interaction value. Bioethanol content average highest in yeast concentration of 12 grams is 19,81% and fermentation time of 168 hours is 19,37%. All research data can be used for designing learning modules on conventional biotechnology material using project based learning. However, before the module design was used on a large scale advisable to test the feasibility and effectiveness test on a small scale.Key Word: Yeast Concentration, Fermentation Time, Barangan Skin Waste, Bioethanol, Learning Module